Resuelve las siguientes ecuaciones
a) -12x = -72
b) x + 4 + x = 18
+ 3
c) x + 3x + 4x =
8
d) 5x - 2 + 2x =
6x + 8
e) 4x + 3x - 2x =
45
f) -x + 4x - 3
= 5 - 2x
g) 2x - 10 = 0
h) 5x + 4 = x - 8
Soluciones: a) x=6, b) x= 17/2 c) x= 1 d) x= 10 e) x= 9 f) x= 8/5 g) x= 5 h) x= - 3
Resuelve las siguientes ecuaciones con paréntesis:
a) x + 2(x - 1) =
4
b) 2(3x - 5) - x -
(2x - 3) = 1 - (2x - 5)
c) 7(x + 2) + 4(x +
3) = 3x + 1
d) 3(x - 3) - 4(2 - 3x)
= 2(1 - 2x)
e) 4x + 1 + 3x - 5 = 2(x - 2) + 30
f) 3(x + 8) = 6(x -
2) + 24
g) 3(x + 8) - (x -
4) = 12
h) 2(4 - x) + 3(4x +
16) = 3
i) 6(x + 8) - 2(x -
4) = 24
j) 6(x - 2) = 3(x + 8) - 24
Soluciones: a) x=2, b) x=13/5, c) x= -25/8, d) x=1, e) x= 22, f) x= 4, g) x= -8, h) x= -53/10, i) x=-4,j)x= 4